IMAGES FROM A LAND DISCOVERED - Lassithiotakis, Ioannis (Design/Arts/Culture, 2020)
The memory of a ship sailing at night, leaving behind a lighted harbor; a deserted house; the empty corner of a cheap seaside restaurant with its white plastic chairs; interiors of ruins; a concrete staircase leading from the earth to infinity; the bow of a ship crossing an empty sea…Images hovering between dream and reality. Images that come nostalgically to remind of a past still alive, often as vivid as the present.